E-COMMERCE PENYEDIA JASA CUCI SEPATU PADA BELL SHOES: Bell Shoes, E-Commerce, Laravel, Laundry, Transactions - Afrizal; Moriana Kurnia, Rizki (LP2M Universitas Nurdin Hamzah, 2023)
E-commerce is all activities related to online transactions that take place via the internet or other electronic networks. Bell Shoes is a business entity engaged in the provision of shoe laundry services. E-Commerce Shoe Washing Service Provider at Bell Shoes is a promotional media application for Bell Shoes shoe laundry to be better known by the wider community, especially in the city of Jambi. This application is designed using Visual Code Studio tools, MySQL database, Laravel 8 Framework and PHP programming language. The expected result of making this application is that it can provide convenience to customers in getting services and information about the services available at Bell Shoes. It also provides convenience for business owners in managing all transactions carried out and in making more detailed financial reports.